PENGETAHUAN SISWA SUPM NEGERI PONTIANAK TENTANG KEANEKARAGAMAN DAN PERLINDUNGAN IKAN HIU DAN PARI - Eka Mardianti; Wolly Candramila; Laili Fitri Yeni (FKIP Universitas Tanjungpura, 2022)
Students' knowledge of the diversity of sharks and rays needs to be known as a conservation effort. One of the fishing locations for sharks and rays (Subclass Elasmobranchii) in West Kalimantan, especially Pontianak, is the TPI Sungai Kakap. This study aims to determine the category of knowledge of SUPM Negeri Pontianak students about the diversity of sharks and rays in Indonesia and West Kalimantan based on data from the catch of sharks and rays (Subclass Elasmobranchii) at TPI Sungai Kakap in October 2021. This study used a survey method by conducting inventory and identification of sharks and rays (Subclass Elasmobranchii) caught by fishermen in the Sungai Kakap TPI. Then the research instrument was made in the form of a questionnaire from the results of the identification carried out. The results of the identification of sharks and rays (Subclass Elasmobranchii) obtained were 9 species, 4 families and 340 individuals. The questionnaire consists of 17 questions with 2 components, namely characteristics and diversity of species and aspects of conservation. The questionnaire made was validated and tested first. The questionnaire survey was conducted on 30 students of class XI SUPM Negeri Pontianak. The knowledge of the SUPM Negeri Pontianak students is at a value of 34 which has a medium category, meaning that their knowledge must be improved again.